Identification and Description of a Silicic Volcaniclastic Layer in Gale Crater, Mars, Using Active Neutron Interrogation. Issue 3 (10th March 2020) - Czarnecki, S.; Hardgrove, C.; Gasda, P. J.; Gabriel, T. S. J.; Starr, M.; Rice, M. S.; Frydenvang, J.; Wiens, R. C.; Rapin, W.; Nikiforov, S.; Lisov, D.; Litvak, M.; et al.
Abstract: The Dynamic Albedo of Neutrons instrument aboard the Mars Science Laboratory rover, Curiosity, has been used to map a stratigraphically conformable layer of high‐SiO 2 material in Gale crater. Previous work has shown that this material contains tridymite, a high‐temperature/low‐pressure felsic mineral, interpreted to have a volcanic source rock. We describe several characteristics including orientation, extent, hydration, and geochemistry, consistent with a volcaniclastic material conformably deposited within a lacustrine mudstone succession. Relationships with widely dispersed alteration features and orbital detections of hydrated SiO 2 suggest that this high‐SiO 2 layer extends at least 17 km laterally. Mineralogical abundances previously reported for this high‐SiO 2 material indicated that hydrous species were restricted to the amorphous (non‐crystalline) fraction, which is dominated by SiO 2 . The low mean bulk hydration of this high‐SiO 2 layer (1.85 ± 0.13 wt.% water‐equivalent hydrogen) is consistent with silicic glass in addition to opal‐A and opal‐CT. Persistent volcanic glass and tridymite in addition to opal in an ancient sedimentary unit indicates that the conversion to more ordered forms of crystalline SiO 2 has not proceeded to completion and that this material has had only limited exposure to water since it originally erupted, despite having been transported in a fluviolacustrine system. Our results, including the conformable nature, large areal extent, and presence of volcanic glass, indicate that this high‐SiO 2 material is derived from the product of evolved magma on Mars. This is the first identification of a silicic volcaniclastic layer on another planet and has important implications for magma evolution mechanisms on single‐plate planets. Plain Language Summary: Using the Dynamic Albedo of Neutrons instrument aboard the Mars Science Laboratory rover, Curiosity, we mapped a silica‐rich layer throughout a small region in Gale crater known as Marias Pass. Previous work has shown that some rocks in Marias Pass contain minerals formed in explosive volcanic eruptions. We determined several key characteristics including orientation, extent, hydration, and elemental composition, which are consistent with material derived from a volcanic deposit. This layer is likely related to nearby silica‐rich material deposited by groundwater along subsurface fractures, and geometric relationships to hydrated silica identified from orbit suggest that this high‐silica layer extends over at least 17 km. Mineralogical data from previous work indicates the crystalline fraction is anhydrous. As such, we interpret the low hydration of this material, attributable to the amorphous (non‐crystalline) fraction, as being consistent with a significant abundance of volcanic glass in addition to other hydrated phases. The presence of volcanic glass indicates that this material has had limited exposure to water since its formation, because glasses tend to preferentially weather. Our results show that this layer is parallel to surrounding rocks, covers a large area, and contains volcanic glass, indicating that it derived from an explosive volcanic product. Key Points: A >1 m thick SiO 2 ‐ and tridymite‐rich layer in Gale crater likely extends over several kilometers This layer is stratigraphically conformable, with low water content consistent with significant volcanic glass This material is consistent with an evolved igneous material deposited in a lacustrine environment